1999
DOI: 10.1046/j.1365-2893.1999.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus genotypes in France: relationship with epidemiology, pathogenicity and response to interferon therapy

Abstract: The aim of this study was to investigate the following in a large population of French patients with chronic hepatitis C: the geographical distribution of hepatitis C virus (HCV) genotypes; the relationship between HCV genotypes and epidemiological characteristics; severity of the disease; and response to interferon (IFN) therapy. Data from 14 tertiary referral centres, corresponding to 1872 patients with chronic hepatitis C, were prospectively collected from 1989 to 1997. HCV genotyping was performed using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
76
5
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(109 citation statements)
references
References 45 publications
24
76
5
4
Order By: Relevance
“…The Genotype 3a was the predominant genotype in this study, which is in line with the findings of studies conducted in India, Pakistan and Nepal (13,14). However, these findings are inconsistent with the results of studies in Saudi Arabia (15), Kuwait (16), France (17), North American countries (18) and South Korea (19). This difference could be due to high prevalence of intravenous drug abuse in the present study (48.33%) because numerous molecular epidemiological studies suggest an association between genotype 3a transmission and history of intravenous drug abuse (13,16,20).…”
Section: Discussionsupporting
confidence: 74%
“…The Genotype 3a was the predominant genotype in this study, which is in line with the findings of studies conducted in India, Pakistan and Nepal (13,14). However, these findings are inconsistent with the results of studies in Saudi Arabia (15), Kuwait (16), France (17), North American countries (18) and South Korea (19). This difference could be due to high prevalence of intravenous drug abuse in the present study (48.33%) because numerous molecular epidemiological studies suggest an association between genotype 3a transmission and history of intravenous drug abuse (13,16,20).…”
Section: Discussionsupporting
confidence: 74%
“…HCV g enotype 1 has been considered a more aggressive genotype, associated with lower clearance rates, decreased susceptibility to current treatments [32][33][34] and in a few cases, associated with a faster progression of HIV disease [51] . Many HCV cohort studies, including the ALIVE cohort in Baltimore are primarily genotype 1 infections [3] .…”
Section: Discussionmentioning
confidence: 99%
“…Other factors such as younger age [3,20] , female gender [21,22] , presence of hepatitis B surface antigen (HBsAg) [3,23] , certain HLA alleles [6,[24][25][26][27][28][29] , and low viral quasispecies diversity [30] have been linked to increased HCV RNA clearance. While African American ethnicity [3,25] , HCV genotype 1 [31][32][33] and co-infections with human immunodeficiency virus-1 (HIV-1) [3] , Human T-Lymphotropic Virus-1 [34] and Schistosoma mansoni [35] have been associated with lower HCV RNA clearance and higher HCV RNA levels. Understanding why and how individuals clear HCV is the key to developing new drugs and an effective vaccine [21] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of the studies, genotype 3 was overall more common in Northern, eastern and Western parts of India, but patients from South India are predominantly infected with genotype 1. [11][12][13][14][15] In contrast, most of the studies from USA, Europe and Japan have reported a prevalence rate of 60%-70% of genotype 1b and 1a in patients with CH-C. 16 HCV treatment responses vary with the genotype, with the highest SVR rates observed for genotype 2, 3 (72-80%) and the lowest rates observed for genotypes 1 and 4 (44-50%). 13,[17][18][19] Our study population also showed similar results as genotype 1 (20%) had significantly low SVR as compared to genotype 3/2 (92.0%).…”
Section: Discussionmentioning
confidence: 96%